E-learning tools and web-resources for teaching reconfigurable systems - Sklyarov, Valery (2006)
The paper shows that the teaching of reconfigurable systems is a complex and difficult process requiring many novel methods and tools to be considered within the same course. This process can be greatly simplified with the aid of the information resources and e-learning tools that have been developed and incorporated into an integrated methodology that includes original evaluation and motivation methods. This methodology has been successfully applied to the teaching of reconfigurable systems for approximately 10 years. The paper discusses the impact of this methodology on such important components of higher education as research activity, postgraduate learning, and training for engineering work in industry.